Stochastic and Deterministic Bundles - Leandre, R. (Український математичний журнал, 2005)
We consider a bundle determined by a classifying map with skeleton smooth in the Chen — Souriau sense. We show that the stochastic classifying map is homotopic to a deterministic classifying map on the Holder loop space.